2022
DOI: 10.3389/fpsyg.2022.959169
|View full text |Cite
|
Sign up to set email alerts
|

Music and neuro-cognitive deficits in depression

Abstract: BackgroundCognitive deficits are one of the core features of major depressive disorder (MDD) that play crucial role in functional recovery. Studies have explored cognitive deficits in MDD, however, given inconsistent results, especially in mild-moderate MDD. Recently, studies have explored music as cognitive ability in various clinical conditions. In MDD, large focus has been on evaluating emotion deficits and just a handful on music cognition. With growing evidence on use of music based intervention to target… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 72 publications
0
2
0
Order By: Relevance
“…Several studies show that cognitive functioning may be impaired during an episode of major depression (Kriesche et al, 2022;Raghavendra et al, 2022;Sankar et al, 2023;Wood-Ross et al, 2023). As stated previously, meta-analysis has shown that cognitive impairment of major depression can persist in remission (Rhee et al, 2024).…”
Section: Neurocognition Performance and Major Depressionmentioning
confidence: 84%
See 1 more Smart Citation
“…Several studies show that cognitive functioning may be impaired during an episode of major depression (Kriesche et al, 2022;Raghavendra et al, 2022;Sankar et al, 2023;Wood-Ross et al, 2023). As stated previously, meta-analysis has shown that cognitive impairment of major depression can persist in remission (Rhee et al, 2024).…”
Section: Neurocognition Performance and Major Depressionmentioning
confidence: 84%
“…There are several studies showing that cognitive functioning may be impaired during episodes of clinical depression (Kriesche et al, 2022;Raghavendra et al, 2022;Sankar et al, 2023;Wood-Ross et al, 2023). These neurocognitive deficits have relevance to the abilities and performance of a pilot.…”
Section: Discussionmentioning
confidence: 99%